Cervical cancer in pregnant women. How does it affect the course of pregnancy. Methods of diagnosis and treatment. - Sosna, Monika; Misiło, Adriana; Mordoń, Krzysztof (Journal of Education, Health and Sport, 2023)
Cervical cancer is now a common occurrence in both non-pregnant and pregnant women. The sooner cancer is diagnosed, the greater the chance of cure and better prognosis for the future. Treatment is used if it is supported by a multidisciplinary team including doctors, midwives, psychologists, psychotherapists, physiotherapists. Diagnostics and methods of treatment of pregnant women for a complex process. These methods must be carefully analyzed and applied in accordance with the guidelines and the implementation of treatment and diagnostics in the event of damage to toxicity and risk to the mother and fetus. Matrials and methods: The literature available on PubMed and Google Scholar was reviewed using the words: „cancer and pregnancy”, „cervical cancer”